Influence of oxyR on Growth, Biofilm Formation, and Mobility of Vibrio parahaemolyticus - Chung, Chun-Hui (Appl Environ Microbiol, 2016)
Vibrio parahaemolyticus is a common marine food-borne enteropathogen. In this study, we examined the antioxidative activity, growth, biofilm formation, and cell mobility of an oxyR deletion mutant and its genetically complementary strain of V. parahaemolyticus. oxyR is the regulator of catalase and ahpC genes. Protection against extrinsic H(2)O(2) and against the organic peroxides cumene hydroperoxide and tert-butyl hydroperoxide was weaker in the deletion mutant than in its parent strain. Expression of the major functional antioxidative genes, ahpC1 and VPA1418, was markedly decreased in the oxyR mutant. Growth of this mutant on agar medium was significantly inhibited by autoclaved 0.25% glucose and by 0.25% dipotassium hydrogen phosphate, 0.5% monosaccharides (glucose, galactose, xylose, and arabinose), or 114.8 mM phosphates. The inhibition of the growth of this oxyR mutant by extrinsic peroxides, autoclaved sugars, and phosphates was eliminated by the complementary oxyR gene or by the addition of catalase to the autoclaved medium, while no inhibition of growth was observed when filter-sterilized sugars were used. The formation of biofilm and swimming mobility were significantly inhibited in the oxyR mutant relative to that in the wild-type strain. This investigation demonstrates the antioxidative function of oxyR in V. parahaemolyticus and its possible roles in biofilm formation, cell mobility, and the protection of growth in heated rich medium.